Blockchain in Taxation: A Systematic Literature Review (2017-2022) - Pradhika Yudha Dharma (Directorate General of Taxes, 2025)
The rapid evolution of digital technologies has positioned the implementation of blockchain technology in the field of taxation as a uniquely compelling and necessary research topic, given the government's need to enhance the efficiency and security of revenue collection. This paper addresses the current research landscape by presenting a comprehensive Systematic Literature Review (SLR), summarizing the diverse studies that explore the intersection of tax systems and distributed ledger technologies. Following a rigorous screening and selection process covering publications from January 2017 to October 2022, the analysis focused on 16 relevant primary studies, drawn from an initial pool of 326 articles. The synthesis of these studies reveals that the most dominant research themes concentrate heavily on the integration of blockchain for Value Added Tax (VAT), represented by six papers, and for broader general tax administration, which accounts for five papers. Despite the identified benefits—such as increased transparency and security—the review also highlights significant challenges. The most frequently cited obstacles to adoption are critical concerns over data privacy issues, high implementation costs, and the persistent oracle problem, which relates to verifying the accuracy of off-chain data submitted to the blockchain.